Advancing Criminal Justice Reform through Restorative Justice: A Narrative Review - Abdulovna, Daryna Dzemish (Sinergi International Journal of Law, 2024)
This study presents a comprehensive narrative review of restorative justice within criminal justice systems, analyzing its potential as a reformative alternative to retributive practices. The review aims to synthesize empirical findings on the impact of restorative justice on recidivism reduction, victim satisfaction, and systemic transformation. Literature was systematically collected using databases such as Scopus, PubMed, and Google Scholar, employing keywords like "restorative justice," "mediation," and "criminal justice reform." Inclusion criteria focused on peer-reviewed studies from 2000 to 2025 exploring mediation mechanisms, institutional integration, and socio-cultural impacts. Results show that restorative justice significantly reduces recidivism, fosters victim healing, and improves community engagement. Mediation involving victims, offenders, and community members enhances accountability, reduces trauma, and reinforces social harmony. Comparative studies reveal that implementation success varies across legal systems, influenced by institutional capacity, legal policies, and cultural values. While some jurisdictions integrate traditional values to enhance restorative outcomes, others face challenges due to rigid bureaucracies and weak inter-agency coordination. This review highlights the urgency of policy reforms to support restorative justice through legislation, training, and community awareness. Digital mediation tools and standardized procedures are recommended for broader access and transparency. The findings emphasize the necessity of cross-sector collaboration, legal alignment, and culturally responsive frameworks. Restorative justice emerges as a viable strategy to advance justice reform, aligning punitive responses with principles of empathy, accountability, and social restoration.